Impacts of navigable flow conditions at the confluence of main and tributary streams of a cross-basin canal with high drop geomorphology—a case study of the confluence section of Qinjiang River in Pinglu Canal - Han, Linfeng; Cheng, Ling; Yu, Tao; Yang, Shengfa; He, Junhui (Frontiers in Water, 2025)
The Pinglu Canal is a cross-basin canal project. The Qinjiang River, serving as a vital tributary of the Pinglu Canal, exhibits a significant elevation differential between its riverbed and the canal bed. This geomorphological disparity exerts a substantial influence on both hydraulic dynamics and navigational parameters within the confluence zone. This study investigates the effects of hydrodynamic conditions—specifically, flow velocity characteristics, lateral velocity distribution, and flow regime—at the confluence section of the tributary of the Qinjiang River. The aim is to ensure navigational safety in the connecting segment of the tributary inflow. Through a 1:50 scale river engineering model experiment, systematic optimization and comparative analyses are conducted using iterative combinations of energy dissipation configurations. This approach aims to address the identified deficiencies related to elevated transverse flow velocities and unstable hydrodynamic patterns in the preliminary design. Subsequent validation through a 1:100 scale undistorted physical model quantitatively confirms the recommended scheme’s efficacy in sediment flux interception at tributary confluences. The findings demonstrate that the implementation of stepped stilling basins and sedimentation basins in the confluent reach of the Qinjiang tributary achieves superior remediation efficacy. This engineering configuration enhances navigational flow conditions within the canal while concurrently provides substantial sediment interception capacity for the tributary. These results offer valuable insights for analogous confluence rehabilitation projects in fluvial systems.